Esperire l’alterità. "Migrantour" tra turismo e riqualificazione. Riflessioni a partire da un’etnografia delle passeggiate interculturali di Porta Palazzo a Torino - Iandolo, Sara (Antropologia Pubblica, 2024)
This work analyzes intercultural tours of Porta Palazzo and their role in building symbolic and economic value around places of multiculturalism. The ethnography of Migrantour, which guides tourists to discover otherness in the “world at home”, has made it possible to maintain two levels of analysis: the first concern of how cultural difference is produced and consumed as a commodity in the tourist experience. The second has to do with the co-production of the place as a touristic attraction: walkers and tourists, when they consume the place and the otherness that marks it, contribute to produce it. The tours encourage mechanisms of aestheticization and exoticization of migrants through selective narratives and cultural stereotypes and the display of objects, food and people, creating symbolic value that big investors capitalize on, contributing to activate gentrification and touristification process. For these reasons, in the case of Porta Palazzo, responsible tourism cannot be entirely separated from mass tourism: on the contrary, the two phenomena are extremely intertwined and very often the former feeds the latter.